Current pharmacotherapy in the newborn - Antonucci R; Porcella A (Dove Medical Press, 2012)
Roberto Antonucci, Annalisa PorcellaDivision of Neonatology and Pediatrics, Department of Medicine, “Nostra Signora di Bonaria” Hospital, San Gavino Monreale, ItalyAbstract: Several drugs are used in newborns in spite of the lack of specific clinical research in this particularly vulnerable population with particular needs. In the newborn, the individual response to a drug in terms of efficacy and safety is highly variable, and predicting drug dosing is complex since rapid physiological changes occurring during the perinatal and early postnatal periods affect the pharmacokinetic profile of many drugs. Neonatal disorders such as renal and hepatic diseases may also have significant implications for drug pharmacokinetics. Therefore, pharmacotherapy in the newborn brings difficulties in accurate drug delivery and carries a high risk of adverse drug reactions. In addition, the neonatal population, especially that treated in neonatal intensive care units, is highly exposed to the risk of medication errors, with potentially serious adverse events. This paper reviews some current issues related to neonatal pharmacotherapy that are of paramount importance for the clinician. In particular, the peculiar pharmacokinetics of drugs during the neonatal period and its clinical implications are discussed. The use of therapeutic drug monitoring to individualize drug dosage and to optimize pharmacotherapy is also described. Finally, the relevant issue of medication errors in neonatology is examined in order to highlight their main causes and key strategies in preventing these type of errors. In the future, pharmacometabolomics and other “omic”sciences could play an important role in designing personalized neonatal health care.Keywords: pharmacotherapy, drugs, pharmacokinetics, therapeutic drug monitoring, medication errors, newborn